2020
DOI: 10.5210/spir.v2020i0.11229
|View full text |Cite
|
Sign up to set email alerts
|

The Virtual Census 2.0: A Continued Investigation on the Representations of Gender, Race and Age in Videogames

Abstract: While many studies suggest media representations of marginalized social groups play a vital role in shaping one’s worldview (Gerbner et al. 1994) or normalizing power imbalances (Harwood and Anderson 2002), videogames continue to privilege characters that are White, adult and male. This paper revisits key questions addressed in Williams, et al.’s “The Virtual Census: Representation of Gender, Race and Age in Videogames” (2009) to examine how representations of gender, race, and age in videogames have changed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…These attitudes are reflected in the representation of female characters within video games. For example, a number of previous studies demonstrate a systematic under-representation of female characters appearing in games [27][28][29][30][31][32] as well as related material, including game covers and marketing [33][34][35]. Many studies have identified that female characters are more likely to be sexualized than male characters [27,29,[36][37][38], and to be positioned in more minor roles [32,39].…”
Section: Introductionmentioning
confidence: 99%
“…These attitudes are reflected in the representation of female characters within video games. For example, a number of previous studies demonstrate a systematic under-representation of female characters appearing in games [27][28][29][30][31][32] as well as related material, including game covers and marketing [33][34][35]. Many studies have identified that female characters are more likely to be sexualized than male characters [27,29,[36][37][38], and to be positioned in more minor roles [32,39].…”
Section: Introductionmentioning
confidence: 99%